2006
DOI: 10.1124/jpet.106.105106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adrenomedullin on Cardiac Oxidative Stress and Collagen Accumulation in Aldosterone-Dependent Malignant Hypertensive Rats

Abstract: We examined the effects of adrenomedullin on cardiac oxidative stress and collagen accumulation in aldosterone-dependent malignant hypertensive rats. Spontaneously hypertensive rats (SHRs) were treated with one of the following combinations for 4 weeks: tap water and vehicle [0.5% ethanol, subcutaneously (s.c.), n ϭ 5], 1% NaCl in drinking water and vehicle (n ϭ 8), 1% NaCl and aldosterone (0.75 g/h s.c., n ϭ 8), and 1% NaCl, aldosterone, and adrenomedullin (1.3 g/kg/h s.c., n ϭ 8). Systolic blood pressure (SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…This histological feature of the oldest SHR would be related to the higher oxidative stress detected in these rats. This hypothesis is supported by recent investigations in other hypertrophy models (69,70), in which a correlation between ROS production and cardiac collagen accumulation was found. Accumulating evidence has suggested that ROS are capable of directly activating intracellular cascades involved in the regulation of hypertrophic growth (71).…”
Section: Discussionsupporting
confidence: 75%
“…This histological feature of the oldest SHR would be related to the higher oxidative stress detected in these rats. This hypothesis is supported by recent investigations in other hypertrophy models (69,70), in which a correlation between ROS production and cardiac collagen accumulation was found. Accumulating evidence has suggested that ROS are capable of directly activating intracellular cascades involved in the regulation of hypertrophic growth (71).…”
Section: Discussionsupporting
confidence: 75%
“…Other studies have further demonstrated that adrenomedulin, a peptide structurally related to CGRP, can act via both CGRP and adrenomedulin receptors to mediate its effects. Adrenomedulin has also been implicated in ROS generation (Yoshimoto et al 1998;Dakhama et al 2004;Rahman et al 2006;Itoh et al 2007;Kim et al 2010). Furthermore, CGRP has been found to play an important role in protecting myocytes, kidney cells, pancreatic B cells, and liver cells from the potentially damaging effects of ROS (She et al 2003;Kroeger et al 2009;Song et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…NADPH-dependent superoxide production was measured by a lucigenin-enhanced chemiluminescence assay (13,27). Briefly, LV tissues were homogenized with Multi-Beads Shocker (YASUI KIKAI, Osaka, Japan) in modified Krebs-HEPES buffer (pH 7.4, 99.01 mmol/L NaCl, 4.69 mmol/L KCl, 1.87 mmol/L CaCl2, 1.20 mmol/L MgSO4, 1.03 mmol/L K2HPO4, 25 mmol/L Na-HEPES, 11.1 mmol/L glucose) containing 10 mmol/L dithiothreitol (DTT), 1 mmol/L phenylmethylsulfonyl fluoride (PMSF), 3 μmol/L pepstatin and 10 μmol/L leupeptin.…”
Section: Nadph Oxidase Activitymentioning
confidence: 99%